A Review on Natural Plant Extract as a Green Inhibitor for Steel Corrosion Resistance - Rampradheep G.S, Raja.K, R. Sruthi (International Journal of Advanced Science and Technology, 2020)
Corrosion is the serious consequence facing in the construction field, to solve the problem completely, the natural plant has been used green inhibitor. The green inhibitor pretends to be more corrosion resistance on the metal surface. The green plants are more effective in reducing the corrosion rate and are very economical in cost and also in every facet of the corrosion problem. The evaluation of the corrosion inhibiting efficiency in the plant extract contains more antioxidant nature, which provides a more noticeable effect in treating the deterioration process. In current trends, the natural plant extract is used in the form of anti -corrosive coating which provides the safeguarding layer on the metal, and the antioxidant compound present in the plant combines with the metal surface and enhances its strength and protects it from the corrosion. Through various analyses, and the basic test the effectiveness of the plant floral part has been detected and extracted through the suitable process without disturbing the antioxidant properties and through the various testing method, the inhibition efficiency is proved and also their inhibition efficiency percentage has been revealed in this paper. Being the plant organs are more effective in treating the corrosion problem, they had been used as green inhibitor for control the corrosion problem. So the green corrosion inhibitor is a more eco-friendly and recyclable natural resource.